The People Reloaded - Tauseef Ahmad Parray (International Institute of Islamic Thought, 2011)
The People Reloaded ‒ an anthology of the multiplicity of voices, belonging to various perspectives, fields, and geographical locations throughout the world, and primarily and principally in the Iran and Iranian diasporas ‒ is edited by Nader Hashemi (of the University of Denver) and Danny Postel (the editor of The Common Review). The book is a definitive selected collection of fifty-three writings and political analyses written by diverse voices interested in and engaged with the struggle for democracy in Iran. The People Reloaded is comprised of key documents, statements, interviews, letters, and essays ‒ and it seeks to capture “an important moment in Iran’s history (xxii).” This book is a rich, consistently engaging anthology that makes an important effort to provide “an intellectual and political roadmap,” which helps the reader in understanding the tumultuous events that have rocked the Islamic Republic since June 2009 ‒ a period when the struggle for the democracy in Iran underwent a “momentous transformation (xi).” The facts, analyses, shadings, and nuances that these essays provide allow the reader to better understand whatever direction Iran can or may take in the future. The editors contribute to the work the introduction and two essays; the remaining essays are those of noted historians, political activists in and out of Iran, and journalists. Among the historians are Ervand Abrahamian, Hamid Dabashi, and Juan Cole; the activists include Ayatollah Mohsen Kadivar, Shirin Ebadi (2003 Nobel Peace Prize winner), and Hossein Bashiriyeh; and the journalists include Roger Cohen, Stephen Kinzer, and Laura Secor. The combined effect is a history of the Green Movement, which includes much of Iran’s revolutionary past and a vision of the future of the Green Movement in its struggle for justice and a voice in the ancient civilization of Iran ...